Kepastian Hukum terhadap Sertipikat Hak Milik Atas Tanah yang Dikuasai oleh Warga Negara Asing akibat Perceraian dalam Perkawinan Campuran - Rahmat Ramadhan; Yurisa Martanti; Iran Sahril (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Discussion on legal certainty regarding land ownership certificates controlled by foreign nationals due to divorce in mixed marriages. The research was conducted using normative juridical methods. The results of the research concluded that mixed marriages between Indonesian citizens (WNI) and foreign citizens (WNA) are increasingly prevalent along with increasing global mobility. However, behind this legally valid relationship, there are complex problems related to ownership of assets, especially land, which can only be owned by Indonesian citizens as regulated in Article 21 paragraph (1) and paragraph (3) of the Basic Agrarian Law (UUPA). Legal certainty does not reflect justice, so to obtain its benefits, Indonesian citizens must sue. This legal certainty is obtained because of the existence of regulations, so that foreign nationals and Indonesian citizens who carry out the divorce according to legal regulations are not allowed to have land ownership certificates are required to sell the land so that it can be divided in two.